1998
DOI: 10.1017/s0022112098002183
|View full text |Cite
|
Sign up to set email alerts
|

Observations of coagulation in isotropic turbulence

Abstract: Turbulent-shear-induced coagulation of monodisperse particles was examined experimentally in the nearly isotropic, spatially decaying turbulence generated by an oscillating grid. The 3.9 μm polystyrene microspheres used in the experiments were made neutrally buoyant and unstable by suspending them in a density-matched saline solution. In this way, particle settling, double-layer repulsion and particle inertia were negligible and the effect of turbulent shear was isolated. The coagulation rate was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 0 publications
4
23
0
1
Order By: Relevance
“…On the other hand, Saffman and Turner [38] obtained a similar value of the prefactor, equal to 1.293, for turbulent-flow conditions and spherical droplets. As was shown by Bäbler et al [39] once the hydrodynamic interactions of the particle on the surrounding fluid are incorporated in the trajectory analysis the value of aggregation rate prefactor reduces significantly, in agreement with experimentally determined values (see, e.g., [32,33,[40][41][42]). The reason for such differences from simple theoretical models is that the theoretical derivations did not include effects of particle interactions, such as hydrodynamic interactions, van der Waals attraction, surface chemistry, etc.…”
Section: Aggregation Kernelsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, Saffman and Turner [38] obtained a similar value of the prefactor, equal to 1.293, for turbulent-flow conditions and spherical droplets. As was shown by Bäbler et al [39] once the hydrodynamic interactions of the particle on the surrounding fluid are incorporated in the trajectory analysis the value of aggregation rate prefactor reduces significantly, in agreement with experimentally determined values (see, e.g., [32,33,[40][41][42]). The reason for such differences from simple theoretical models is that the theoretical derivations did not include effects of particle interactions, such as hydrodynamic interactions, van der Waals attraction, surface chemistry, etc.…”
Section: Aggregation Kernelsupporting
confidence: 82%
“…Since its dependency on the shear rate can be measured experimentally [32,33] it is possible to separate shear-rate dependency from other mentioned parameters and write it in the following form: [30,[34][35][36] and experimental measurements [32,33] for large primary particles confirmed that the aggregation rate prefactor α SA ij (G) in Eq. (4) is weakly dependent on the shear rate.…”
Section: Aggregation Kernelmentioning
confidence: 95%
“…We restrict the consideration to the channel core where the nearly homogeneous and isotropic flow conditions allow the application of the collision model developed. The particles are regarded as a mono-size suspension, and, consequently, the droplet size growth is treated as a sequence of the formation of doublets due to the loss of singlets (e.g., see Brunk et al, 1998). This simple coalescence model gives a rather crude approximation to the real agglomeration process and it may be solely used for estimating the droplet mean size.…”
Section: Particle Agglomeration Due To Coalescencementioning
confidence: 99%
“…The observed rate of coagulation can be compared to theoretical models of physically based coagulation processes to estimate the mean sticking efficiency in the natural system. While this method of estimating sticking efficiency has been successfully tested for clay particles (Hunt 1982) and colloids (Brunk et al 1998), it has yet to be tested for systems containing algal cells.…”
mentioning
confidence: 99%